2016
DOI: 10.1080/00380768.2016.1196119
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of agricultural products and soils with radiocesium derived from the accident at TEPCO Fukushima Daiichi Nuclear Power Station: monitoring, case studies and countermeasures

Abstract: Five years have passed since the accident at Tokyo Electric Power Company Fukushima Daiichi Nuclear Power Station that was triggered by the Great East Japan Earthquake on 11 March 2011. Severe damage to agriculture and the environment is still of great concern in Japanese society. We review the contamination status of agricultural products and soils, decontamination efforts and countermeasures to reduce radiocesium concentration in soil and crops, as well as the responses of Japanese ministries. Since rice is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…The soil RCs concentrations at the intervention value of 5 kBq kg −1 (Yamaguchi et al ., ) are most relevant because soils with RCs concentrations > 5 kBq kg −1 are currently not used for rice cultivation. The dissolved 137 Cs concentration in river water in the Fukushima‐affected area ranged between 0.002 and 0.59 Bq l −1 (geometric mean 0.038 Bq l −1 ) in 2012–2013 (Eyrolle‐Boyer et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The soil RCs concentrations at the intervention value of 5 kBq kg −1 (Yamaguchi et al ., ) are most relevant because soils with RCs concentrations > 5 kBq kg −1 are currently not used for rice cultivation. The dissolved 137 Cs concentration in river water in the Fukushima‐affected area ranged between 0.002 and 0.59 Bq l −1 (geometric mean 0.038 Bq l −1 ) in 2012–2013 (Eyrolle‐Boyer et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The damage from the Tsunami 2011 in a coastal area was very severe in Fukushima Prefecture, and damaged farmland amounted to 4,571 ha. Moreover, the accident at Tokyo Electric Power Company Fukushima Daiichi Nuclear Power Station caused not only contamination of farmlands and associated products (Yamaguchi et al, 2016), but also delayed the restart of farming by longterm avoidance of polluted areas. Accordingly, Fukushima Prefecture Government rapidly started a radioactive materials measurement team (Fukushima Prefectural Government, 2016) and Fukushima Prefecture Government, NARO and other institutions and universities around the country worked on the development of countermeasure technology for radioactive pollution (Shinano, 2016).…”
Section: Nursery Trials In Fukushima Prefecturementioning
confidence: 99%
“…On the other hand, many reports revealed that application of potassium (K + ) fertilizer is very effective and more practical in reducing radiocesium uptake by paddy rice 7, 8 . Kato et al .…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the radiocesium concentrations in the soil, several options are recommended for decontamination: topsoil removal, fine-textured topsoil removal using water, and topsoil burying 2 , 7 . On the other hand, many reports revealed that application of potassium (K + ) fertilizer is very effective and more practical in reducing radiocesium uptake by paddy rice 7 , 8 . Kato et al .…”
Section: Introductionmentioning
confidence: 99%